Toleransi Berdasarkan Cerita Rakyat Tallu To Sala Dadi di Toraja - Rantesalu, Marsi Bombongan; Iswanto, Iswanto (Institut Agama Kristen Negeri Toraja, 2018)
Tolerance is described as a concept of cultural phenomena that are integrated through religious life. Conflict as an internal problem while the challenges of the times (globalization) are goals that must be answered through a spirit of tolerance. The concept that will be analyzed is based on folklore tallu to sala 'dadi in Toraja. This study intends to examine the structure of the tallu to sala 'dadi story, and the tolerance value contained in the story. The theory used in this study is the semiotic social theory. While the method used is a qualitative method of content analysis and hermeneutic methods. As a result, data was obtained that the story was of a novel type, which revealed the struggles of human life in living everyday life. The values of tolerance contained include the value of acceptability and understanding that are paired with togetherness and complementarity. Based on these findings, it can be defined that tolerance is the attitude of accepting and understanding shortcomings and differences through togetherness and complementarity.AbstrakToleransi dideskripsikan sebagai konsep fenomena budaya yang terintegriasi melalui kehidupan beragama. Konflik sebagai masalah internal sedangkan tantangan jaman (globalisasi) merupakan tujuan yang harus dijawab melalui semangat toleransi. Konsep itulah yang akan dianalisa berdasarkan cerita rakyat tallu to sala’ dadi di Toraja. Penelitian ini bermaksud mengkaji struktur ceritera tallu to sala’ dadi, dan nilai toleransi yang terkandung dalam ceritera tersebut. Teori yang digunakan dalam penelitian ini ialah teori semiotik sosial. Sedangkan metode yang digunakan ialah metode kualitatif analisis kontent serta metode hermeneutik. Hasilnya, diperoleh data bahwa cerita tersebut berjenis novel, yang mengungkapkan pergumulan hidup manusia dalam menjalani hidup sehari-hari. Adapun nilai-nilai toleransi yang terkandung meliputi nilai keberterimaan dan kesepahaman yang dipadankan dengan kebersamaan dan saling melengkapi. Berdasarkan temuan tersebut dapat di definisikan bahwa toleransi adalah sikap menerima dan memahami kekurangan dan perbedaan melalui kebersamaan dan sikap saling melengkapi.